The Individual Green-Washing Effect in E-Mobility: Emotional Evaluations of Electric and Gasoline Cars - Jansen, Petra; Schroter, Franziska Anna; Hofmann, Philipp; Rundberg, Ronja (Frontiers in Psychology, 2021)
Due to the focus on climate change, sustainable transportation, and especially e-mobility is one of the most important topics nowadays. In this study the affective explicit and implicit evaluative responses towards electric and gasoline cars are investigated. 165 participants (103 cisgender women, 62 cisgender men) completed an explicit and implicit affective rating task towards pictures of electric and gasoline cars, measurements of sustainability, and future and past behaviour and mindfulness. The results showed a positive emotional rating for the electric cars compared to the gasoline cars only for the explicit rating but not for the implicit ones. For all participants those who owned and those who did not own a car, the explicit rating was predicted by the willingness to purchase an electric car in the future whereas the implicit ratings are correlated to different aspects of mindfulness. This indicates that several different factors should be considered in the development of promotion campaigns for the advantage of sustainable mobility behaviour.